Does the Growth Rate Hypothesis Apply across Temperatures? Variation in the Growth Rate and Body Phosphorus of Neotropical Benthic Grazers - Moody, Eric K.; Rugenski, Amanda T.; Sabo, John L.; Turner, Benjamin L.; Elser, James J. (Frontiers in Environmental Science, 2017)
The growth rate hypothesis predicts that organisms with higher maximum growth rates will also have higher body percent phosphorus (P) due to the increased demand for ribosomal RNA production needed to sustain rapid growth. However, this hypothesis was formulated for invertebrates growing at the same temperature. Within a biologically relevant temperature range, increased temperatures can lead to more rapid growth, suggesting that organisms in warmer environments might also contain more P per gram of dry mass. However, since higher growth rates at higher temperature can be supported by more rapid protein synthesis per ribosome rather than increased ribosome investment, increasing temperature might not lead to a positive relationship between growth and percent P. We tested the growth rate hypothesis by examining two genera of Neotropical stream grazers, the leptophlebiid mayfly Thraulodes and the bufonid toad tadpole Rhinella. We measured the body percent P of field-collected Thraulodes as well as the stoichiometry of periphyton resources in six Panamanian streams over an elevational gradient spanning approximately 1100 m and 7 °C in mean annual temperature. We also measured Thraulodes growth rates using in situ growth chambers in two of these streams. Finally, we conducted temperature manipulation experiments with both Thraulodes and Rhinella at the highest and lowest elevation sites and measured differences in percent P and growth rates. Thraulodes body percent P increased with temperature across the six streams, and average specific growth rate was higher in the warmer lowland stream. In the temperature manipulation experiments, both taxa exhibited higher growth rate and body percent P in the lowland experiments regardless of experimental temperature, but growth rate and body percent P of individuals were not correlated. Although we found that Thraulodes from warmer streams grew more rapidly and had higher body percent P, our experimental results suggest that the growth rate hypothesis does not apply across temperatures. Instead, our results indicate that factors other than temperature drive variation in organismal percent P among sites.